Sensitivity, Specificity and Predictive Values of Cytological and Microbiological Findings of Endometrial Biopsy, Cytobrush and Low Volume Uterine Lavage in Relation to Endometrial Histology in Barren Mares - Mathew, Agnus; Hadiya, KK; Patel, DM (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This study was carried out on 10 infertile barren mares to evaluate the sensitivity, specificity, predictive values and agreement (kappa value) of cytological and microbiological findings of three diagnosing techniques of endometritis, viz., endometrial biopsy (EB), cytobrush (CB) and low volume uterine lavage (LVL) in relation to endometrial histology. When histological examinations from EB were used as “the best standard,” the sensitivity of cytology from EB, CB and LVL technique was 0.33, 0.50 and 0.50; specificity 0.75, 1.00 and 0.75; positive predictive value 0.66, 1.00 and 0.75, and negative predictive value was 0.42, 0.57 and 0.50, respectively. The sensitivity of bacteriology from EB, CB and LVL technique was 0.83, 0.83 and 1.00; the specificity was 0.75, 0.75 and 0.50; positive predictive value 0.83, 0.83 and 0.75, and the negative predictive value was 0.75, 0.75 and 1.00, respectively. In all the cases, the sensitivity of the bacteriology was found to be higher than the sensitivity of cytology. When the results of cytological and bacteriological examinations were combined, no any increase in the sensitivity was found. Bacteriology and cytology from CB showed the highest positive predictive value demonstrating that a positive result is an accurate indication of endometritis. Sensitivity values were always higher if smears were evaluated according to PMNs to epithelial cell ratio, and the highest values were observed in specimens collected from CB and LVL. The evaluation of cytological smears based on counting PMNs in relation to epithelial cells was a better method for diagnosis of endometritis than counting the number of PMNs per high power microscopic field (k value 0.07-0.47 vs. 0.00). The agreement of the diagnosis of endometritis between the three techniques of the collection was from fair to poor and between the different criteria adopted to evaluate smears was always poor. However, the agreement of the diagnosis of endometritis by the microbial culture was moderate between the three techniques of the collection (k value 0.55-0.58).